Lime stabilized Malaysian cohesive soils - Kassim, Khairul Anuar (Faculty of Civil Engineering, UTM, 2004)
This paper highlights the essential tests for assessing the suitability of lime for stabilizing soils and typical changes in soil characteristics due to modification and stabilization processes with respect to mineralogical influences. The reasoning behind the mechanism of lime clay reaction on the compressive strength development of stabilized soils has been established. Clay with acidic origin exhibit less significant increase in compressive strength compared to clay with high intensity of kaolinite and with alkaline origin. In general, lime contents instituted, ranging from 3% to 6%, have contributed to a significant increase in unconfined compressive strength, from 2.5 to 11 times of the untreated soils. The formation of calcium aluminates silicate hydrate (CASH) observed from XRD test, after 14 days, indicates the early formation of new product, due to lime-soil reaction. The effectiveness of stabilization process has been found to be dependent on the quality of the lime, clay fraction, mineralogy and the alkalinity of the soil.